Impact of emotional abuse on eating disorder psychopathology: A multiple mediation analysis - Barone Eugenia; Carfagno Marco; Marafioti Niccolò; Bello Rosaria; Arsenio Eleonora; Marone Luigi; Volpicelli Antonio; Cascino Giammarco; Monteleone Alessio Maria (Comprehensive Psychiatry, 2024)
Introduction: Childhood maltreatment, particularly emotional abuse (EA), has been identified as a significant risk factor for the development of eating disorders (EDs). This study investigated the association between EA and ED symptoms while considering multiple potential mediators. Methods: Participants included 151 individuals with Anorexia Nervosa (AN), 115 with Bulimia Nervosa (BN), and 108 healthy controls. The Childhood trauma questionnaire, the Toronto Alexithymia scale, the Behavioral inhibition System, and the Eating Disorder Inventory 2 scale were completed before treatment. A mediator path model was conducted in each group: EA was set as independent variable, eating symptoms as dependent variables and ineffectiveness, sensitivity to punishment, alexithymia, and impulsivity as mediators. Results: In individuals with AN, impulsivity emerged as a significant mediator between EA and desire for thinness and bulimic behaviors. Conversely, in individuals with BN, sensitivity to punishment was found to mediate the association between EA and dissatisfaction with one's body.Ineffectiveness and difficulty identifying emotions were identified as transdiagnostic mediators in both clinical groups. No mediation effect was found in healthy individuals. Discussion: The simultaneous assessment of multiple mediators in a unique model outlines the complex interplay between childhood EA and ED psychopathology. Improving ineffectiveness, emotion identification, sensitivity to punishment and impulsivity and exploring their relations with early emotional abuse may represent treatment targets in individuals with EDs and childhood trauma.